Burkholderia pseudomallei in Sarawak, Malaysian Borneo, Remains Highly Susceptible to Trimethoprim-Sulfamethoxazole Despite Resistance to Its Individual Components - Liana Lantong, Sumbu; Tonnii Sia, Loong Loong; Ooi, Mong-How; Anand, Mohan; Wong, Jin-Shyan; Yuwana, Podin (MDPI, 2026)
Burkholderia pseudomallei, the causative agent of melioidosis, is endemic in Sarawak, Malaysian Borneo, where it is represented by a unique gentamicin-susceptible population. Despite trimethoprim-sulfamethoxazole (co-trimoxazole) being the cornerstone of eradication therapy, emerging reports of elevated minimum inhibitory concentrations (MICs) among Sarawak isolates have raised concerns over its clinical efficacy. We performed a retrospective and comprehensive antibiotic susceptibility assessment of clinical B. pseudomallei isolates from hospitals across Sarawak. Susceptibility to trimethoprim-sulfamethoxazole was determined using disk diffusion and the E-test, interpreted by both CLSI and EUCAST guidelines. Resistance to the individual components, trimethoprim and sulfamethoxazole, was characterized by broth microdilution. The results demonstrated a high prevalence of trimethoprim-sulfamethoxazole susceptibility, with 96.3% of isolates susceptible by CLSI criteria and 97.6% by EUCAST criteria. Interestingly, broth microdilution revealed that resistance to trimethoprim and sulfamethoxazole individually did not confer resistance to the synergistic combination. Our analysis validated CLSI guidelines as the most reliable standard for antimicrobial resistance surveillance in this region. This study provides evidence that trimethoprim-sulfamethoxazole remains effective for melioidosis treatment in Sarawak, offering crucial reassurance to clinicians. The paradoxical finding of susceptibility to the drug combination despite resistance to its individual components underscores the critical importance of the synergistic activity of trimethoprim-sulfamethoxazole and highlights the need for further investigation into the molecular basis of resistance in this distinct B. pseudomallei population.